Kajian fungsi irigasi sebagi masukan sistem pertanian organik: studi kasus di pantai Selatan D.I.Yogyakarta=The Study on Irrigation Function as Organic Farming System - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT The study was directed to analyze irrigation display as pattern of soil water and nitrate distribution that caused by the using of farm manure along with water irrigation in the sandy soil through mathematical model. Research was done until 60 days. Soil sample were brought from Pandansimo, which placed at lysimeter. Animal manure placed at the surface of soil. Irrigation water was applied with discharge 150 cm3/ minute for 1 hour everyday. Validation of the model indicated that statistically and graphically the mathematical model of simultaneous distribution of both nitrate and water in unsaturated soil was suitable to applied for prediction of nitrate distribution on coastal sandy soil with animal manures. Result of sensitivity analysis showed that the parameter which the most sensitive was initial condition. The chart of soil water distribution showed that the soil profile from depth 10 cm - 40 cm indicated that soil water contents increased until 60 days, but decreased at 50 cm until 30 days, than increased until 60 days. At 60 cm, soil water contents decreased until below of initial condition. Prediction of the nitrate distribution with irrigation discharged 30 cm3/minute for 5 minute everyday for 60 days, indicated that nitrate wasn't leached at 60 cm of depth.